Real-time monitoring of environmental conditions in Deep Metalliferous Mines: VOD operational readiness - Ngcibi, Asabonga Kenneth (My University, 2022)
The purpose of this report is to outline the results of an empirical study conducted at South Deep on locating underground environmental sensors. The environmental monitoring sensors were installed at South Deep, as an enabler for various modernisation techniques, namely; real-time monitoring for workplace re-entry time optimisation and ultimately automation of underground operations. The literature shows that VOD systems have great benefits including energy savings, health and safety improvements and productivity improvements. The knowledge gap in the implementation of such systems has led to many hard rock mines missing out on these benefits. The industry has continued to rely on outdated means of monitoring the underground environment. This is due to the lack of SA manufactured real-time sensors and knowledge of how select and position these sensors. This means that even attempting to modernise SA hard rock mines is limited by the knowledge ceiling. The project followed a quantitative methodology, as the objectives are quantifiable and any credible results need to be compared to the base case. A base case was established by gathering quantitative data from the mine which include environmental surveys and energy audits. This data was used to form models for simulations required for planning. The real-time monitoring installation project at South Deep Mine was critical in establishing the operational readiness of the mine for VOD systems. With a POC undertaken at a single production corridor, the learning costs of the project were kept at a minimum. The system is an enabler for various modernisation projects such as VOD and automation. The sensors were selected based on criteria focused on system compatibility with the communication network. The requirements of the system, accuracy & reliability, durability & robustness and the size of the instruments were also critical parameters. The health and safety of the personnel will depend on these systems, hence the validation of errors and accuracies is required before commissioning is required. After selection, locating these sensors is another critical step for real-time monitoring projects. With global monitoring used at South Deep, critical monitoring points had to be established while ensuring the tunnel uses, dimensions and plans are considered before choosing the exact location. After testing, the mine reduced workplace re-entry times by 35 min, a 29% reduction, by implementing remote early-entry examination. This translates to an increase of 8.6% in effective shift time. Theoretically, this should translate to a production gain of the same amount, which equates to an additional ZAR 600 million in revenue. Theoretical energy savings based on a scheduled control of the auxiliary system can save the mine up to ZAR 28 million per year, a 41% reduction in energy costs. Through the real-time monitoring system, the mine will also improve the health and safety standards at the mine. By practising remote early-entry examinations through the real-time monitoring of the system, the mine will reduce the risk rating of the activity from level nine (9) to level three (3).
A dissertation submitted in fulfilment of the requirements for the degree of Masters Science in Engineering to the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2022